Effects of freeze-drying and spray drying processes on functional properties of phosphorylation of egg white protein - Lili, Liu; Huan, Wang; Guangyue, Ren; Xu, Duan; Dan, Li; Guangjun, Yin (International Journal of Agricultural and Biological Engineering, 2015)
Egg white protein (EWP) was phosphorylated with Sodium Tripolyphosphate (STP) at pH 4.5. Freeze drying and spray drying were used for drying purpose and the effects of these drying methods on the functional properties were investigated. The functional properties of native and modified proteins were also determined. The results demonstrated that phosphorylation of EWP markedly improved its functional properties, and that it was more effective for the food industry. The freeze-dried STP-EWP powders were superior in terms of solubility, emulsion stability, water holding capacity, oil and water absorption capacity and heat gel strength than spray-dried STP-EWP powders. The results in viscosity showed no significant differences between freeze-dried and spray dried. The spray-dried powders were better in terms of foaming ability and foam stability than freeze-dried powders. However, the spray drying required the longest time to produce. Freeze drying was found to be the best method in terms of production of modified EWP powders with superior functional properties. Keywords: freeze drying, spray drying, egg white protein, phosphorylation, functional properties DOI: 10.3965/j.ijabe.20150804.1942 Citation: Liu L L, Wang H, Ren G Y, Duan X, Li D, Yin G J. Effects of freeze-drying and spray drying processes on functional properties of phosphorylation of egg white protein. Int J Agric & Biol Eng, 2015; 8(4): 116－123.